Pengaruh Implementasi Kebijakan Standar Operasioal Prosedur Terhadap Kinerja Pegawai Pada Sekretariat Kota Manado - PURBA, IRA ELBERTNA; KIYAI, BURHANUDDIN; RUMAPEA, PATAR (JURNAL ADMINISTRASI PUBLIK, 2014)
This study starts from the problem that: the extent to which the implementation of astandard operating procedure policies on employee performance at Regional Secretariat Manado.Thus, this research aims: to analyze the effect of policy implementation of standard operatingprocedures on employee performance at Secretariat Manado.This study uses a quantitative approach to the application of descriptive and explanatory. informationcollected through questionnaires distributed to the technique 112 respondents, and is equipped withobservation and documentation techniques, and then analyzed by applying the technique of frequencytables analysis, multiple linear regression and simple linear regression.Based on the analysis of data, it is known that: the distribution of respondents on all variables, bothindependent variables and the dependent variable / dependent as communication, resources andattitudes disposisi or executor implementation / application of the SOP, the average being "high" to be"moderate", while variables - bureaucratic structure variables and the implementation or applicationof SOP is still in the category of "moderate" tends to be high "high". Then the dependent variable ordependent (employee performance) is the category of "high" tend to be "moderate".Thus, it can be concluded that the implementation of a standard operating procedure policies itssignificant positive effect on employee performance and are jointly or simultaneously all theindependent variables (communication, resources, dispositions / attitudes and bureaucratic structure)has a positive and significant impact on the implementation of SOP at Secretariat Manado City.Keywords: Implementation of policies, Standard Operational Procedures, employee performan